Pengaruh Customer Relationship Management dan Service Quality terhadap Customer Loyalty pada Toko Permata Silver Kersana - Sri Utami Pebrianingsih; Alfred Heriman Setio; Sigit Pamungkas (Jurnal Sistem Informasi Akuntansi (JASIKA), 2025)
The effect of Customer Relationship Management (CRM) and Service Quality (SQ) on Customer Loyalty (CL) at the "Permata Silver" Store in Kersana, Brebes, Central Java was examined in this study. A quantitative approach was adopted, with data collected from 100 respondents selected through accidental sampling. Data were gathered using both online and offline questionnaires, and multiple linear regression analysis was employed for data evaluation. It was found that both Customer Relationship Management (CRM) and Service Quality (SQ) exert a statistically significant and positive influence on Customer Loyalty (CL). The calculated t-values were 3.711 and 44.285, respectively, both exceeding the critical t-table value of 1.985. Additionally, the p-values (0.000) were below the significance threshold of 0.005. When evaluated simultaneously, the two independent variables demonstrated a significant joint effect on Customer Loyalty (CL), as indicated by an F-statistic of 1408.516, which surpassed the critical F-table value of 3.090. The coefficient of determination (R²) was determined to be 0.967, indicating that 96.7% of the variance in Customer Loyalty (CL) can be explained by variations in Customer Relationship Management (CRM) and Service Quality (SQ). Consequently, higher levels of Customer Relationship Management (CRM) and Service Quality (SQ) are associated with increased Customer Loyalty (CL).